2010
DOI: 10.2166/hydro.2010.089
|View full text |Cite
|
Sign up to set email alerts
|

Pipe roughness calibration in water distribution systems using grey numbers

Abstract: This paper presents a procedure based on the use of grey numbers for the calibration (with uncertainty) of pipe roughness in water distribution systems. The pipe roughness uncertainty is represented through the grey number amplitude (or interval). The procedure is of a wholly general nature and can be applied for the calibration (with uncertainty) of other parameters or quantities, such as nodal demands. In this paper, for the purpose of roughness calibration, a certain number of nodal head measurements made u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 56 publications
0
12
0
2
Order By: Relevance
“…However, SCADA systems are beyond the reach of most water utilities in developing countries. In recent years, researchers have identified the necessity to include uncertainty in the calibration of WDS models including pipe roughness coefficients and nodal demands (Alvisi & Franchini 2010;Giustolisi & Berardi 2on). Uncertainty quantification of model parameters such as nodal demands implies a profound knowledge of the system and the availability of sufficiently long time series data.…”
Section: Methodsmentioning
confidence: 99%
“…However, SCADA systems are beyond the reach of most water utilities in developing countries. In recent years, researchers have identified the necessity to include uncertainty in the calibration of WDS models including pipe roughness coefficients and nodal demands (Alvisi & Franchini 2010;Giustolisi & Berardi 2on). Uncertainty quantification of model parameters such as nodal demands implies a profound knowledge of the system and the availability of sufficiently long time series data.…”
Section: Methodsmentioning
confidence: 99%
“…Some parameter adjustments have been proposed to obtain a good calibration model. One of the approaches is adjusting the pipe roughness coefficient with sufficiently accurate nodal demand data [10][11][12]. There have also been a few methods suggested to consider adjustment of both the pipe roughness coefficient and the nodal demand [13] in model calibration of water distribution networks.…”
Section: Introductionmentioning
confidence: 99%
“…The same number of equations are required as the number of unknowns. The other types of methods for calibration of the model are implicit approaches (e.g., Ormsbee 1989;Lansey and Basnet 1991;Datta and Sridharan 1994;Greco and Giudice 1999;Greco and Di Cristo 1999;Lansey et al 2001;Kapelan 2002;Lingireddy and Ormsbee 2002;Bascià and Tucciarelli 2003;Kapelan et al 2007;Koppel and Vassiljev 2009;Alvisi and Franchini 2010), in which field-observed and measured parameters are treated as known parameters and directly used in the model analysis. The implicit approach requires that the number of flow and pressure measurements exceed the number of unknowns.…”
Section: Introductionmentioning
confidence: 99%